Everolimus plus reduced calcineurin inhibitor prevents de novo anti-HLA antibodies and humoral rejection in kidney transplant recipients: 12-month results from the ATHENA study - Arns, Wolfgang; Philippe, Aurélie; Ditt, Vanessa; Hauser, Ingeborg A.; Thaiss, Friedrich; Sommerer, Claudia; Suwelack, Barbara; Dragun, Duska; Hillen, Jan; Schiedel, Christiane; Elsässer, Anja; Nashan, Björn (Frontiers in Transplantation, 2023)
Background: Studies prospectively monitoring de novo donor-specific antibodies (dnDSAs) and their clinical impact are sparse. This substudy of ATHENA was initiated to evaluate the effect of everolimus (EVR) or mycophenolic acid (MPA) in combination with reduced calcineurin inhibitor (CNI, tacrolimus [TAC] or cyclosporine [CsA]) on the formation of human leukocyte antibodies (HLA), including dnDSA, and the impact on clinical outcomes in kidney transplant (KTx) recipients. Methods: All eligible patients were randomized 1:1:1 to receive either EVR+TAC, EVR+CsA or MPA+TAC, with basiliximab induction plus steroids after transplantation up to Month 12. The incidence of dnDSA by treatment group and the association with clinical events were evaluated descriptively as an exploratory objective in the intent-to-treat (ITT) and per-protocol (PP) populations with at least one antibody assessment. Results: Overall, none of the patients in the EVR+TAC group had either dnDSA or antibody mediated rejection (PP or ITT population) and only one patient with dnDSA in the TAC+MPA group had antibody mediated rejection. Conclusion: The EVR regimen was comparable to MPA regimen with an extremely low incidence of dnDSA over 1 year of treatment.